Panorama da produção de potássio e o potencial brasileiro - a exploração dos depósitos - FERREIRA, Pedro Furtado (2017)
The potassium element (K) is positioned in the first family of the Periodic Table and classified as an atomic number 19 alkali metal, it is a solid metal at room temperature, ductile, has high electrical conductivity and increases with the temperature rise, chemically very reactive, and therefore is not found freely in nature, only as compounds of evaporitic origin (main deposits) and constituents of the potassium silicate rocks. Approximately 95% of the world’s potassium is destined for agriculture, an important macronutrient for food products and is considered a strategic mineral for Brazil due to its high external dependence, since approximately 90% of the potassium consumed comes from outside. They also have other applications in the chemical industry as in the manufacture of detergents, soaps, special glasses, etc. The potassium minerals found in silica rocks are insoluble and difficult to extract, but there is much research for use in agriculture as fertilizers. The main reserves are found in the states of Minas Gerais and São Paulo. Potassium of evaporitic origin is the main deposits explored internationally, beind found three deposits in Brazil, two in the State of Amazonas, in the municipality Nova Olinda do Norte operated by Vale Fertilizantes S.A and another in the world-class city of Autazes, operated by the company Potássio Brasil S.A. The third deposit is located in the State of Sergipe, in the city of Rosario do Catete, which is the only one in operation and insufficient for Brazilian self-sufficiency. Therefore, the Brazilian production of potash is still below its potential, given the existence of deposits not yet plowed for production. Also the political tax situation is not favorable for the Brazilian producers, discouraging strategic ventures for the country, in case of the Project Carnalita de Sergipe that is suspended.